ROLE OF ATRIAL NATRIURETIC PEPTIDE IN VARIOUS CONDITIONS - VISHAL KUMAR VISHWAKARMA; JEETENDRA KUMAR GUPTA; SHAIBA SANA QURESHI; VIMAL AGRAWAL. (International Journal of Pharma and Bio Sciences, 2016)
Atrial natriuretic peptide (ANP) was discovered twenty years ago and has a crucial role in regulating blood pressure, body fluid homeostasis and maintaining cardiovascular function. Evidences from animal model reported a decrease in estrogen level via ANP gene inhibition. Estrogen induces ANP release via ER dependent mechanism from the heart and prevents cardiac hypertrophy. It has been reported that mice lacking ANP exhibit high blood pressure due to loss of cGMP (vasodilator). ANP also inhibit L- type Ca+2 channel in the heart, induce vasorelaxation in arteries, decrease sympathetic nervous system activity and suppress RAAS. It has been reported that a potent vasoconstrictor (Endothelin) augments ANP secretion and up regulates ANP messenger RNA. Reduced ANP contributes in increased fluid retention in obese individuals. Pro-BNP has shown an independent risk factor for CVD with diabetes. Natriuretic peptides cause augmentation in GFR, thus contributing in glomerular hyperfilteration in diabetic rat heart. ANP improves the attenuated cardioprotective effect of ischemia preconditioning by increasing the activity of NO in diabetic rat heart. Over the past decade, ANP became an essential tool in the management of various metabolic disorders. In this article, we have focused on the physiological effects of ANP referring hypertension, hyperlipidemia, diabetes mellitus, estrogen deficiency, ischemia reperfusion injury, ischemia preconditioning and endothelins.